Perancangan Sistem Inventarisasi dan Perbaikan Barang Berbasis Web Menggunakan Metode RAD - Diva Ayu Pramista; Putri Indah Suryani; Andria .; Hani Atun Mumtahana (CV. ITTC INDONESIA, 2026)
Inventory and repair management are essential aspects in supporting organizational operational performance. The UPT Workshop of Signal, Telecommunication, and Electricity Unit (Sintelis) at PT. Kereta Api Indonesia (Persero) Daop 7 Madiun still applies a manual recording system for inventory and repair management, which may cause data inaccuracies, reporting delays, and difficulties in data retrieval. This study aims to design and develop a web-based inventory and repair information system to improve efficiency and data accuracy. The research method used is Research and Development with the Rapid Application Development (RAD) approach, which consists of requirement planning, design workshop, and implementation stages. Data were collected through observation, interviews, and documentation studies. The results indicate that the developed system is able to manage inventory and repair data in an integrated manner and generate reports automatically. System testing using the black box testing method shows that all system functions operate according to user requirements. Therefore, the developed information system can serve as an effective solution to support inventory and repair management at the Sintelis Unit.